Pengaruh Work Life Balance Dan Komitmen Karyawan Terhadap Kinerja Karyawan Siloka Tasikmalaya - Alrasyid, Fahmi; Rahwana, Kusuma Agdhi; Risana, Dudu (Jurnal Pakar Manajemen, 2024)
This research aims to determine the influence of Work Life Balance and Employee Commitment on the Performance of Kopi Siloka Tasikmalaya Employees. The method used was quantitative with a research sample of 35 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the results of this research, it shows that Work Life Balance and Employee Commitment simultaneously have a positive and significant effect on Employee Performance. Work Life Balance partially has a significant effect on employee performance. Employee Commitment partially has a significant effect on Employee Performance.